1990
DOI: 10.1093/carcin/11.8.1349
|View full text |Cite
|
Sign up to set email alerts
|

DNA adduction by phenol, hydroquinone, or benzoquinone in vitro but not in vivo: nuclease P1-enhanced 32P-postlabeling of adducts as labeled nucleoside bisphosphates, dinucleotides and nucleoside monophosphates

Abstract: The carcinogenicity of benzene has been considered to be in part mediated by its chemically reactive metabolic product benzoquinone (BQ), which is formed from the intermediary metabolites phenol and hydroquinone (HQ). We have evaluated the DNA-binding capability of these chemicals in vitro and in vivo by postlabeling. Treatment of rat Zymbal glands in culture with phenol and HQ or direct reaction of BQ with DNA produced DNA adducts, which were detectable by the nuclease P1-enhanced 32P-postlabeling assay as 5'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…112 In contrast to the clearly demonstrated formation of DNA adducts by HQ exposure in vitro, evidence for similar adduction in whole animal experiments is absent. Using two variations of the 32 P-postlabeling assay, Reddy et al 113 failed to demonstrate adducts in bone marrow, Zymbal gland, liver, or spleen DNA from female SD rats after HQ exposure (75 or 150 mg/kg/day, 4 days, p.o.). No increase in adducts by postlabeling was seen in kidney DNA from male or female F344 rats exposed to 50 mg/kg/day HQ, p.o., for 6 weeks.…”
Section: Macromolecular Binding and Redox Reactionsmentioning
confidence: 99%
“…112 In contrast to the clearly demonstrated formation of DNA adducts by HQ exposure in vitro, evidence for similar adduction in whole animal experiments is absent. Using two variations of the 32 P-postlabeling assay, Reddy et al 113 failed to demonstrate adducts in bone marrow, Zymbal gland, liver, or spleen DNA from female SD rats after HQ exposure (75 or 150 mg/kg/day, 4 days, p.o.). No increase in adducts by postlabeling was seen in kidney DNA from male or female F344 rats exposed to 50 mg/kg/day HQ, p.o., for 6 weeks.…”
Section: Macromolecular Binding and Redox Reactionsmentioning
confidence: 99%
“…Lutz and Schlatter (1977) administered benzene by inhalation and suggested that with respect to covalent binding to hepatic DNA, benzene was among the poorest binding agents. Reddy et al (1990Reddy et al ( , 1994 treated rats with benzene by gavage for 5 days per week for up to 10 weeks at doses ranging from 200 to 500 mg/kg/day. At the end of 10 weeks they observed three faint spots in the post-abeling assay when he examined the Zymbal gland, but not in the marrow or other organs.…”
Section: B Binding To Dnamentioning
confidence: 99%
“…32P-postlabeling studies have demonstrated DNA adduct formation in the liver of New Zealand rabbits74) and in the bone marrow of B6C3Fi mice 75) treated with benzene ; however, Reddy et al [76][77][78] were unable to detect the formation of DNA adducts in various tissues of either Sprague-Dawley rats or B6C3Fi mice administered benzene or its hydroxylated metabolites.…”
Section: Genotoxicity (Mutagenicity)mentioning
confidence: 99%